2021
DOI: 10.3389/fnbeh.2021.654469
|View full text |Cite
|
Sign up to set email alerts
|

A New Paradigm for Training Hyperactive Dopamine Transporter Knockout Rats: Influence of Novel Stimuli on Object Recognition

Abstract: Attention deficit hyperactivity disorder (ADHD) is believed to be connected with a high level of hyperactivity caused by alterations of the control of dopaminergic transmission in the brain. The strain of hyperdopaminergic dopamine transporter knockout (DAT-KO) rats represents an optimal model for investigating ADHD-related pathological mechanisms. The goal of this work was to study the influence of the overactivated dopamine system in the brain on a motor cognitive task fulfillment. The DAT-KO rats were train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
0
5
0
1
Order By: Relevance
“…In this study we demonstrate, not for the first time [ 22 , 40 , 41 ], the ADHD-like phenotype of DAT-KO rats: in the Hebb–Williams maze, compared to WT, DAT-KO rats made more errors, took a longer time and traveled a longer distance to reach the goal box and exhibited perseverative returns. Errors, time and distance are parameters that may be interpreted in different ways to indicate hyperactivity, impulsivity, deficient attention and working memory, while the number of return runs indicates repetitive (perseverative) behaviors of DAT-KO rats.…”
Section: Discussionmentioning
confidence: 67%
“…In this study we demonstrate, not for the first time [ 22 , 40 , 41 ], the ADHD-like phenotype of DAT-KO rats: in the Hebb–Williams maze, compared to WT, DAT-KO rats made more errors, took a longer time and traveled a longer distance to reach the goal box and exhibited perseverative returns. Errors, time and distance are parameters that may be interpreted in different ways to indicate hyperactivity, impulsivity, deficient attention and working memory, while the number of return runs indicates repetitive (perseverative) behaviors of DAT-KO rats.…”
Section: Discussionmentioning
confidence: 67%
“…DAT -knockout rats show impairment in learning the cognitive task, however, their hyperactivity does not prevent the capability to learn a non-spatial cognitive task in the appearance of novel stimuli ( Kurzina et al, 2021 ). Importantly, DAT genetic hypofunction in mice produced alterations consistent with ADHD, but not with schizophrenia or bipolar disorders ( Mereu et al, 2017 ) in one study, but it was shown in another study that DAT silencing in the rat produces abnormalities in the prefrontal-midbrain and in striato-cerebellar circuits leading to motor hyperactivity and compulsive-like behaviors applicable for ADHD, schizophrenia, and obsessive-compulsive disorder ( Reinwald et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Flagel et al (41) showed that novelty-seeking behaviors can be predictive for a behavioral strategy involved in Pavlovian conditioning: high responders to novelty consistently learn a sign-tracking CR whereas low responders to novelty consistently learn a goal-tracking CR. However, there are controversial studies for the DAT-KO rats in novelty detection (23,42).…”
Section: Hyperdopaminergia Is Associated With Specific Impairments Of...mentioning
confidence: 99%
“…Comparable to DAT-KO mice (21), DAT-KO rats weigh less than heterozygote (HT) and wild-type (WT) rats, demonstrating dramatically increased locomotor activity and prominent motor and oral stereotypies (19,22). Mutant rats also display impaired working memory (8), changes in learning an object recognition task (23), and altered male sexual behavior (24).…”
Section: Introductionmentioning
confidence: 99%